2019
DOI: 10.1097/paf.0000000000000457
|View full text |Cite
|
Sign up to set email alerts
|

Applied Force During Prone Restraint

Abstract: Introduction It has been suggested that law enforcement officer (LEO) weight on the backs of prone subjects may cause asphyxia. Methods Law enforcement officers used their agency-trained “local” single- and double-knee techniques, the “Wisconsin” 3-Point Ground Stabilization, and the Human Factor Research Group Inc single-knee tactical handcuffing techniques, and the weight force was measured. Results Forty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…We discuss here a subset of police arrest-related deaths with no obvious cause of death and involving prone restraint. It has been reported that the rate of arrest-related deaths is approximately one death per every 1000 arrests [28]. Prone restraint related deaths have been observed to occur two to three times per year in Ontario, England and Wales, Los Angeles and the Netherlands [49][50][51][52], each with populations exceeding 10 million.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We discuss here a subset of police arrest-related deaths with no obvious cause of death and involving prone restraint. It has been reported that the rate of arrest-related deaths is approximately one death per every 1000 arrests [28]. Prone restraint related deaths have been observed to occur two to three times per year in Ontario, England and Wales, Los Angeles and the Netherlands [49][50][51][52], each with populations exceeding 10 million.…”
Section: Discussionmentioning
confidence: 99%
“…[17,[25][26][27]. Kroll has pointed out that the entire weight of an officer is not necessarily applied to the back of the chest [28] and that there is a difference between static and dynamic compressional forces; he developed a biomechanical model suggesting that an adult male can tolerate up to 572 lb. of static pressure for a short period before developing rib fractures and a flail chest [29].…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…36 This initial observation was followed by an evaluation of WF applied to prone mannequins by an LEO with three different single-knee techniques and one double-knee technique. 37 This group reported that the application of a single knee creates an average WF of 23.7–32.9 kg, independent of the weight of the LEO. The double-knee technique created a WF that was 23.3 kg plus 24% of the weight of the LEO.…”
Section: Ventilationmentioning
confidence: 96%
“…Additionally, Kroll, Brave, Kliest, Ritter, Ross, & Karch measured the weight force of placing one or two knees on a Simulaids Rescue Randy training mannequin placed in the prone position, which replicated the prone restraint process. 31 Respondents placed either one knee on the shoulder blade area of the mannequin or placed one knee on the shoulder blade area and the other knee on the lower back. It was determined that the two-knee method applied slightly more weight than the one knee method.…”
Section: Scientific Research and Prone Restraintmentioning
confidence: 99%